Characteristics and quality of life of people living with comorbid disorders in substance use recovery residences - Elizabeth O. Obekpa; Sheryl A. McCurdy; Kathryn R. Gallardo; Serena A. Rodriguez; Cecilia Ganduglia Cazaban; H. Shelton Brown; James J. Yang; J. Michael Wilkerson (Frontiers Media S.A., 2024)
BackgroundOpioid use disorder (OUD) is associated with significant morbidity and mortality; however, research on physical and mental health comorbidities and health-related quality of life (HRQoL) among people taking medication for OUD (MOUD) and living in recovery residences is sparse. We investigated the prevalence of comorbidities and examined which EQ-5D-5L HRQoL dimensions are most affected by these comorbidities.MethodsData were collected from 358 residents living in 14 Texas-based recovery residences from April 2021 to June 2023. The EQ-5D-5L descriptive system comprises five dimensions (mobility, self-care, usual activities, pain/discomfort, anxiety/depression). Each dimension has five levels of perceived problems, dichotomized into "No problems" (level 1) and "Any problems" (levels 2-5) for analyses. Cross-sectional analyses of residents' characteristics, comorbidities (categorized as mental health disorders or association with major body systems), and EQ-5D-5L dimensions were conducted using Chi-squared or Student t-tests. Multivariable logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs).ResultsThe mean [SD] age of residents was 36.0 [8.9]. Most residents were non-Hispanic White (68.7%), male (59.7%), unemployed (66.3%), and engaged in polysubstance use (75.4%). The most frequently reported comorbidities were mental health (26.5%), respiratory (26.3%), neurological (19.3%), cardiovascular (18.2%), and musculoskeletal (17.0%) disorders. The most reported HRQoL problems were anxiety/depression (75.8%) and pain/discomfort (53.2%). In the unadjusted regression models, all comorbidities, except mental health (negative association) and digestive (no association) disorders, were positively associated with HRQoL problems. The usual activities dimension was the most affected by comorbidities, followed by mobility and pain/discomfort. Increasing age was positively associated with cardiovascular disorders (aOR = 1.06; 95% CI = 1.03-1.10), musculoskeletal disorders (aOR = 1.03; 95% CI = 1.00-1.06), mobility problems (aOR = 1.05; 95% CI = 1.01-1.09), and pain/discomfort problems (aOR = 1.02; 95% CI = 1.00-1.05). Illicit drug use was positively associated with mobility problems (aOR = 3.36; 95% CI = 1.20-9.45). Neurological (aOR = 2.71; 95% CI = 1.38-5.33) and musculoskeletal (aOR = 2.57; 95% CI = 1.25-5.29) disorders were positively associated with pain/discomfort problems. MOUD duration was negatively associated with mental health disorders (aOR = 0.14; 95% CI = 0.08-0.22) but not HRQoL.ConclusionsComorbidities significantly predict HRQoL among individuals with OUD. Our findings highlight the need for an integrated care model to treat OUD and comorbidities to sustain recovery and improve health and HRQoL.